Practice, Practice, Practice ... Secure Programmer! (Journal of The Colloquium for Information Systems Security Education, 2015)
One of the major weaknesses in software today is the failure to practice defensive or secure programming. Most training programs include only a shallow introduction to secure programming, and fail to integrate and emphasize its importance throughout the curriculum. The addition of an ongoing, practical, mentored "clinic" or Secure Programming Clinic (SPC) is one way of addressing this lack without adding significantly to an already stretched curriculum. In order to properly design this clinic, it is important to identify the knowledge, skills and abilities (KSAs) needed to develop effective programmers. This paper describes the results of a Delphi Study undertaken to determine the primary knowledge areas in secure programming.